Titania-based polymeric sol for enhanced robustness in self-cleaning surfaces. - Chan, Bao Li. (2009)
Robust self-cleaning glass in this project is achieved by coating a titania-based polymeric sol on the glass surface and subsequently calcined at 500oC. A thin solid transparent film with good robustness 5B (based on ASTM 339D Elcometer scratch test) was acquired. The robust coating was achieved by using two organic modifiers, namely acetyl acetone and 3-glyciodoxypropyl-trimethoxysilane (GPTMS). Results show that addition of acetyl acetone to the polymeric sol aided in achieving superhydrophilicity but affected the robustness of coating; while addition of GPTMS helped to enhance robustness but compromised photocatalytic activity. Based on experimental results, an optimal ratio of 1.5 mole ratio for GPTMS with respect to 200 moles of titania and 80 mole ratio of acetyl acetone with respect to 1 mole of Imidazole were obtained for optimal combination of photocatalytic activity, hydrophilicity, coating robustness and coating transparency.